Analysis of the Morphometic and Hydrological Characteristics of the Wadi Shaal Basin and Its Secondary Basins - Shida Juma, Ashjan Gheab; Hamid, Dali Khalaf (Journal of Tikrit University for Humanities, 2024)
The study aims to estimate the volume of torrential rainwater discharge, and as a result of the difficulty in estimating torrential waves in the Wadi Shaal basin, the methods used to estimate the amount of torrential rain must be developed, specifically in unmonitored basins. Because of this, the Snyder model was used to find out this through mathematical models to estimate the volume of the torrents in the water basins in a way that simulates the method of the hydrological system in the basin. We note that the calculated value of the water basin response period to precipitation (TP) is estimated per hour for the study area, as the lowest possible time period during which rain falls was (1.1) hours in (W21) basin. (W24, W27) respectively, and after that the surface runoff begins, while the maximum possible period of time during which rain falls is (1.8) hours, as the maximum period of time in basin (W1, W31) hours, as we note the maximum amount of torrential flow reaches (47.8) m3/s in Basin (W9) and the lowest amount of torrential flow reaches (8.2) m3/s in basin (W12).